2006
DOI: 10.1134/s000629790607008x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lipopolysaccharides and lipids A from some marine bacteria on spontaneous and Escherichia coli LPS-induced TNF-α release from peripheral human blood cells

Abstract: Some endotoxic properties of lipopolysaccharides (LPS) and lipids A (LA) from the marine bacteria Marinomonas communis ATCC 27118(T), Marinomonas mediterranea ATCC 700492(T), and Chryseobacterium indoltheticum CIP 103168(T) were studied. The preparations tested were shown to have high 50% lethal doses (4 microg per mouse for LPS from M. mediterranea and more than 12 microg per mouse for two other LPS and LA from C. indoltheticum) and were moderate (371 +/- 37 pg/ml at 10 microg/ml of C. indoltheticum LPS), wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Similarly, M. communis ATCC 27118 T lipid A (Figure g) was found to possess phosphate only on the reducing glucosamine entity and to bear five short acyl chains, three primary 10:0(3‐OH) and two secondary 10:0 (replaceable with one 12:0) and 10:0(3‐OH) . Intriguingly, Vorobeva et al demonstrated that M. communis ATCC 27118 T lipid A was unable to induce TNF‐α release from peripheral human blood cells, whereas it was capable of inhibiting TNF‐α release induced by E. coli LPS …”
Section: Lps In Gram‐negative Extremophiles: Structural and Biologmentioning
confidence: 97%
“…Similarly, M. communis ATCC 27118 T lipid A (Figure g) was found to possess phosphate only on the reducing glucosamine entity and to bear five short acyl chains, three primary 10:0(3‐OH) and two secondary 10:0 (replaceable with one 12:0) and 10:0(3‐OH) . Intriguingly, Vorobeva et al demonstrated that M. communis ATCC 27118 T lipid A was unable to induce TNF‐α release from peripheral human blood cells, whereas it was capable of inhibiting TNF‐α release induced by E. coli LPS …”
Section: Lps In Gram‐negative Extremophiles: Structural and Biologmentioning
confidence: 97%
“…As a integral part of the Outer Membrane, structural changes can occur in lipid A in response to environmental stressing conditions, mostly with regards to the fatty acids composition, to counterbalance the alterations effected by physical and chemical agents [20,21]. Lately, great attention has been paid to marine bacteria lipids A and LPSs, since they have often shown low levels of toxicity [22]. It is known that some lipid A from Gramnegative bacteria may also express antagonistic activity toward the innate immune system, competing with toxic LPSs for the active sites of the PRRs and protein mediators, thus, limiting their immunological reactivity [23].…”
Section: Lps Molecular Architecture and Activitymentioning
confidence: 99%
“…( a ) Lipid А of P. haloplanktis АТСС 14399 Т bacteria [17], where R = 3-OH-11:0, 3-OH-12:0, 3-OH-13:0, 3-OH- iso -11:0, 3-OH- iso -12:0 acid; ( b ) Lipid A of M. сommunis ATCC 27118 T [21] (I), M. vaga ATCC 27119 T [20] (II) and M. mediterranea АТСС 700492 Т [24] (III) bacteria, where (I) −R = C12:0 acid; (II) −R = С10:0, С12:0 or С12:1 acids; (III) −R = 3-ОН-С10:0 acid; С4′ atom in the molecule of this lipid A is replaced with the residue of phosphoric acid; ( c ) Lipid A C. scophthalmum CIP 104199 Т [22] and C. indoltheticum CIP 103168 Т [24]. …”
Section: Lipid a Chitosan And Carrageenan—marine Compounds With Amentioning
confidence: 99%
“…Due to these findings, biological properties of marine LPSs and lipid As with unusual structures (Figure 3b(I),3b(III),3c) are studied using ex vivo bioassays in human whole blood with tumor necrosis factor-α (TNF-α) as a marker of cell activation [24]. TNF-α has been shown to be the most important inflammatory cytokine that mediates multiple immunopathological features of LPS-induced sepsis [23].…”
Section: Lipid a Chitosan And Carrageenan—marine Compounds With Amentioning
confidence: 99%
See 1 more Smart Citation